Information systems development: methodologies, techniques and tools - Avison, David; Fitzgeerald, Guy (Boston, Massachusetts : McGraw Hill Education, 2006)
Covers Information Systems Development Context, the Systems Development Lifecycle, Themes of Systems Development, Techniques, Methodologies, Tools and Toolsets and Issues and Frameworks. This title analyzes context, issues and real-world problems associated with information systems development
Part 1: Introduction -- 1.Context -- 2.Information systems development -- Part 2: The life cycle approach -- 3.Information systems development life cycle -- Part 3: Themes in information systems development -- 4.Organisational themes -- 5.People themes -- 6.Modelling themes -- 7.Rapid and evolutionary development -- 8.Engineering themes -- 9.External development -- Part 4: Techniques -- 10.Holistic techniques -- 11.Data techniques -- 12.Process techniques -- 13.Object-oriented techniques -- 14.Project management techniques -- 15.Organizational techniques -- 16.People techniques17.Techniques in context -- Part 5: Tools and Toolsets-- 18.Tools -- 19.Toolsets -- Part 6: Methodologies -- 20.Process-oriented methodologies -- 21.Blended -- 22.Object-oriented methodologies -- 23.Rapid development methodologies -- 24.People-oriented methodologies -- 25.Organisational-oriented methodologies -- 26.Frameworks -- Part 7: Methodology issues and comparisons -- 27.Issues -- 28.Methodology comparisons --Bibliography -- Index
Includes bibliographical references and index.
Keywords: SYSTEM DESIGN